A safer chopping board / Eric Tan Zhi Hao … [et al.] - Tan Zhi Hao, Eric; Yan Ming, Voon; Si Bao, Khor; Yong Xin, Ang; Zi Xuan, Lee; Wai Jian, Ng; Sin Chuen, Tan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The experiment was inspired when one of our members, Eric Tan Zhi Hao observed his mother changing the chopping board from plastic to wooden. Therefore, he tried to figured out which would be cleaner after using the boards this project was carried out to choose a safer and more hygienic chopping board. The best chopping board does not pollute the environment or harm it in any way and by using a good chopping board that last longer will be more economical in a long run.